A possible universal role for mRNA secondary structure in bacterial translation revealed using a synthetic operon - Yonatan Chemla (Nature Portfolio, 2020)
The mechanisms for regulating translation re-initiation in bacteria remain poorly understood. Here, the authors screened a library of synthetic operons and identified a ribosome termination structure that modulates re-initiation efficiency and which is conserved across bacteria.